Research progress of chondroitin sulfate and chondroitin sulfate proteoglycan in diabetic kidney disease - ZHANG Min; HU Chun; WU Xiao-yan (Linchuang shenzangbing zazhi)
Diabetic kidney disease(DKD) is a serious complication of diabetes mellitus and an important global public health problem. Due to the complex pathogenesis of DKD, there is still few specific and effective treatment measures. Increased extracellular matrix(ECM) is the most important pathological feature of DKD. Chondroitin sulfate/chondroitin sulfate proteoglycan(CS/CSPG) is an essential component of ECM, including a large family of biological active molecules with complex structures and various functions. They play important functional and regulatory roles in physiology and pathology. Existing evidence has shown that there is CS/CSPG remodeling in DKD, and several CSPGs have significant effect on the pathogenesis and progression of DKD, involving inflammation, fibrosis, and lipid metabolism. Regulation of CS/CSPG might be useful for the prevention and treatment of DKD, and further exploration of CS/CSPG probably bring new breakthroughs in the treatment of DKD.